PENGARUH POLA ASUH SANTRI TERHADAP MOTIVASI BELAJAR SANTRI DI MTs DARUNNAJAH 2 CIPINING - Nur Khafidoh; Arizqi Ihsan Pratama; Mustafa Zahir; Ahmad Farid (JURNAL ILMIAH NUSANTARA, 2025)
Santri Parenting is a parenting pattern that applies in the family, interactions between parents and children during parenting activities, forms of parenting patterns include authoritarian parenting, democratic parenting, and permissive parenting. individual / someone to carry out activities that can support the achievement of goals, and the circumstances contained within a person that encourage activities to achieve a goal This research approach uses quantitative survey method. The sample research in this study used a population of all students of class VIII and IX of MTs Darunnajah 2 Cipining 33 students. Data collection techniques were carried out by questionnaires and documentation. The research procedure begins with the preparation of the grid, the preparation of the instrument, conducting the trial, the test results are tested for validity and reliability, improving the instrument, then the instrument is used to collect data. The results of the calculation are obtained by the regression equation = 25,898 + 0,416 X. And the results of regression testing using product moment regression, it can be seen that the regression price (ryx) = = 0,930 with a probability value (Sig. Fchange) = 0,000. Because the value of sig. Fchange < 0.05, then the decision is H1: accepted and H0 is rejected. It means significant. So it can be concluded that the Parenting Santri has a positive and significant effect on the Students' Learning Motivation. The value of the simple correlation coefficient of rxy = 0.930 and the significance test of variance was 86.4% while the remaining 13.6% Students' learning motivation was influenced by other variables.